(untitled) (Ciudades, 2018)
There are people around the world that dreams of Praga, Kyoto or Granada, very few with Montreal. It is just. If the people of a city don’t look after their way of life, they can’t expect foreigners to do it. In the architecture, landscape or urbanism fields, Montreal isn’t an authority and I don’t want to offer it as a role model. But neither am I looking for role models for Montreal. Rather I’m trying to establish a dialogue between region and cultural representatives that are also not authorities, among whom the conquest of such an authority doesn’t seem to be as urgent as the elaboration of appropriate ideas or practices within their own territories. In this context, the lack of authority of Montreal paradoxically becomes a window.